2021
DOI: 10.1158/1940-6207.capr-20-0542
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Breast Density Change During Menopause and the Risk of Breast Cancer in Korean Women

Abstract: Background: The aim of this study was to investigate the relationship between changes in breast density during menopause and breast cancer risk. Methods: This study was a retrospective, longitudinal cohort study for women over 30 years of age who had undergone breast mammography serially at baseline and postmenopause during regular health checkups at Samsung Medical Center. None of the participants had been diagnosed with bre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Although density is an accepted intermediate marker of breast cancer risk, studies of change in density are limited. Previous studies have used reader-dependent, subjective measures of density and categorical density data (fatty, scattered, heterogeneously dense, and extremely dense in accordance with BI-RADS) . Previous studies have also been based on analysis of digitized radiographic images, which are of lower image quality than standard digital mammograms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although density is an accepted intermediate marker of breast cancer risk, studies of change in density are limited. Previous studies have used reader-dependent, subjective measures of density and categorical density data (fatty, scattered, heterogeneously dense, and extremely dense in accordance with BI-RADS) . Previous studies have also been based on analysis of digitized radiographic images, which are of lower image quality than standard digital mammograms .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used reader-dependent, subjective measures of density and categorical density data (fatty, scattered, heterogeneously dense, and extremely dense in accordance with BI-RADS). 7,[17][18][19][20][21] Previous studies have also been based on analysis of digitized radiographic images, 7,22,23 which are of lower image quality than standard digital mammograms. 24,25 Furthermore, changes in breast density in these studies were often assessed from comparison of only 2 time points.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of breast density used in these studies are summarized in Table 1 . BI-RADS (six studies) [ 28 30 , 32 , 33 , 36 ] and Cumulus (five studies) [ 25 , 26 , 34 , 35 , 42 ] were the most commonly used methods for density assessment. Automated assessments were used on digital mammograms.…”
Section: Resultsmentioning
confidence: 99%
“…Automated assessments were used on digital mammograms. Studies differed in the view used to forecast the overall breast cancer risk, with some only using the craniocaudal (three studies) [ 26 , 35 , 40 ] or mediolateral oblique (four studies) [ 23 , 25 , 31 , 34 ] while others considered both (seven studies) [ 24 , 27 , 28 , 32 , 36 , 38 , 39 ]. The number of cases included in each study ranged from a low of fourty five cases [ 28 ] to a high of 22,781 in a Korean cohort study as shown in Supplementary Table 1 [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation